Maintenance Analysis of Ripple Mill Machine Using PERT Method at PT Ujong Neubok Dalam - Aulia Perlijar; Masykur (Jurnal Inotera, 2023)
The purpose of this research is to control time and to anticipate the completion time of maintenance so that it is not late at PT Ujong Neubok Dalam (UND), and also to improve the implementation of maintenance both as cleaning, lubrication and as periodic checks. In carrying out its production, the company has various machine variations, one of which is the Ripple mill machine. In carrying out ripple mill machine maintenance using the PERT treatment method. The PERT method , or project evaluation and review technique, is a management science model for project planning and execution. The results showed that scheduling on a ripple mill machine was 23 hours or 95.49 % of the normal time. With a very high duration of performance, the greater the possibility of damage occurring, from the analysis that has been carried out, to minimize the damage that occurs to the ripple mill machine, the thing that must be done is to check the ripple mill machine every hour to ensure that there is no damage that can cause the ripple machine mill stopped working. When repairing a Ripple mill machine there are several components that must be provided such as Lubricants, Bearings, V-belt-SPB 2630Lw, Ripple Plate, Pully B3x5, Space Ring, Rotor axle, and 4mm MH360 Welding Wire. As for the work steps, the maintenance starts with checking the axle rotor and immediately following the other components. This maintenance is carried out every 3 months, except for the Ripple Plate and Pully B3x5, because these 2 components are replaced once every 6 months.